COMPARISON OF UNDERWATER IMAGE PROCESSING AND RESTORATION USING SEA- THRU AND HAZE-LINES ALGORITHM - Alifiani, Annisa; Pratama, Nugrah R; Akbarani, Tresna N; Hanif, Muhammad Abdillah N; Ramdan, Nurul; Puspitarani, Yan (CENTRAL ASIA AND THE CAUCASUS, 2022)
The picture which is taken without good lighting will have a shortcoming such as low contrast and discoloration. The lack of light received by objects is usually affected by the position of the object that might be out of camera range or disturbed by fog or water. In this research, we compare image processing and restoration algorithms to restore underwater images that have low contrast and discoloration compared to the real object. The sample images that we use in this restoration process are taken from the Sea-Thru dataset. The results of this research will display the results of the restoration of each algorithm and analyze the comparison of color restoration, transmission restoration, air-light estimation, and counting the RGB channel. With all comparisons, the strengths and weaknesses of the Sea-Thru and Haze-Lines algorithms will be shown, which are the Sea-Thru result is more successful in displaying object colors clearly but still has shortcomings when the angle of sampling image is down, while the Haze-Lines result has more stable in any angles of sampling image.